2000
DOI: 10.1016/s0735-1097(00)00758-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced peripheral vasodilation in humans after a fatty meal

Abstract: We concluded that eating a fatty meal induces vasodilation and increases resting and stimulated FBF and that these observations are probably mediated by postprandial changes in insulin and/or triglyceride levels. The metabolic changes that occur after meals are not associated with impaired endothelial nitric oxide release in the conduit arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
82
5
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 25 publications
15
82
5
1
Order By: Relevance
“…These authors also showed that the attenuation of FMD can be abolished by folic acid pre-treatment, which could be attributed to an increase of nitric oxide production. These findings are in contrast with the earlier mentioned results from studies in healthy volunteers showing a vasodilatory response after a high-fat meal [108]. This could be explained by differences in meal composition resulting in different insulin induced nitric oxide mediated vascular responses.…”
Section: Biochemical and Physiological Responses To Mealcontrasting
confidence: 99%
See 1 more Smart Citation
“…These authors also showed that the attenuation of FMD can be abolished by folic acid pre-treatment, which could be attributed to an increase of nitric oxide production. These findings are in contrast with the earlier mentioned results from studies in healthy volunteers showing a vasodilatory response after a high-fat meal [108]. This could be explained by differences in meal composition resulting in different insulin induced nitric oxide mediated vascular responses.…”
Section: Biochemical and Physiological Responses To Mealcontrasting
confidence: 99%
“…Applying this technique in persons with and without diabetes, the vascular response to different meals has been studied. In healthy volunteers a fatty meal has been shown to induce vasodilatation and to increase forearm blood flow [108]. These changes could be related to the insulin and triglyceride responses.…”
Section: Biochemical and Physiological Responses To Mealmentioning
confidence: 99%
“…In young and middle aged subjects, a well-defined response to nutrient intake is increased limb arterial blood flow (Raitakari et al 2000) but as we reported previously, such responses are reduced or absent in older people ). Here we have again shown that age-related decrements in LBF are associated with impairments in muscle MBV responses to feeding, findings that are consistent with reports of decrements in fed-state forearm MBF (inferred from indirect measurements) (Skilton et al 2005) and also the absence of increased muscle MBF in older people fed EAA and sucrose (Timmerman et al 2012).…”
Section: Discussionsupporting
confidence: 55%
“…Another study [43] proposed that the apparent reduction in FMD after a meal high in saturated fat is actually the result of peripheral vasodilation (measured as an increase in basal artery diameter), rather than a change in endothelial function in itself, and this pattern was confirmed in some [44][45][46] but not all [23,33,47] recent studies. In the present study, neither baseline artery diameter nor peak artery diameter were significantly changed after high-fat meals that are rich in unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 93%